Synthesis of 1-Azaspiro[4.5]deca-1,3-dienes from N-Propargylic β-Enaminones in Basic Medium - Karadeniz, Eda; Zora, Metin (Synthesis, 2019)
A facile, efficient and unprecedented method for the synthesis of spiro-2H-pyrroles is reported. When reacted with 1-ethynylcyclohexylamine, α,β-alkynic ketones produced cyclohexane-embedded N-propargylic β-enaminones, which in the presence of cesium carbonate underwent nucleophilic cyclization to afford 1-azaspiro[4.5]deca-1,3-diene derivatives in good to excellent yields. This cyclization was found to be general for a variety of cyclohexane-embedded N-propargylic β-enaminones and demonstrated good tolerance to a broad range of aliphatic, aromatic and heteroaromatic groups with electron-withdrawing and electron-donating substituents. The decoration of pyrrole compounds with a spiro framework may exhibit potential for the synthesis of molecules of pharmacological interest.
Keywords: pyrroles; 2H-pyrroles; N-propargylic β-enaminones; spiro compounds; nucleophilic cyclization